Rodzina Gierków na Górnym Śląsku jako przykład "czerwonej arystokracji" PRL w świetle literatury przedmiotu. Wstęp do problematyki = The Family of Edward Gierek in Upper Silesia as an example of the "red aristocracy" of PRP in the light of the literature on the subject. Introduc - Małkiewicz, Andrzej; Kuczer, Jarosław; Domke, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The family of Edward Gierek we can treat as a "red aristocracy". In the communist Poland we called at this term families of the VIP from establishment. They life were much easier and com- fortable then the others. They have easier start, education and, sometimes, gained fortunes.
Keywords: elita społeczna - Polska; PRL; Gierek, Edward (1913-2001); Gierek, Adam (1938- ); Gierek-Łapińska, Ariadna (1938- ); historia społeczna; the Elite of PRP; social history